Highly dispersed AuPd alloy nanoparticles immobilized on UiO-66-NH2 metal-organic framework for the detection of nitrite. (20th November 2016) - Yang, Juan; Yang, Lite; Ye, Huili; Zhao, Faqiong; Zeng, Baizhao
Abstract: In this work, highly dispersed AuPd alloy nanoparticles (NPs, 3–6 nm) decorated amino-functionalized Zr(IV)-based metal–organic framework (i.e. UiO-66-NH2 ) was prepared via a novel adsorption/reduction method in ethanol-water solution. In this process, the UiO-66-NH2 acted as both supporting platform and protective agent. The pores of UiO-66-NH2 could limit the aggregation and migration of AuPd alloy NPs. The resulting AuPd/UiO-66-NH2 catalyst possessed large specific surface area and excellent stability and dispersity in aqueous media. When it was used to construct a nitrite sensor, the composite material exhibited higher catalytic activity than the metal counterparts (i.e., Au/UiO-66-NH2 and Pd/UiO-66-NH2 ) due to the strong metallic synergistic effect. The electrochemical study demonstrated that the AuPd/UiO-66-NH2 based sensor had an extended linear response concentration range of 0.05–5666  μ M for nitrite detection, with a detection limit of 0.01  μ M. It was successfully applied to determine nitrite in sausage and pickle samples.